(NoPPORTUNISTI^ESKIE INFEKCII (B. :s (NsOWREMENNYE ASPEKTY PNEWMOCISTNOJ INFEKCII W aRMENII (B/s - (NmEJMARQN(B, (NmANIK aNDRANIKOWNAs ((NeREWAN (B:s (Nb(B. (NI(B.,s, 2005)
(NrEZ@ME(B: (NARM(B., (NANGL(B.s
(NaWT(B. (NIZD(B.s
(NbIBLIOGR(B.: (NS(B. 225-246 (272 (NNAIM(B.)s
Keywords: (NmEDICINAs; (NiNFEKCIONNYE BOLEZNIs; (Nspids; (NpNEWMOCISTOZs -- (NrESPUBLIKA aRMENIQs; (NoPPORTUNISTI^ESKIE INFEKCIIs; (NoPPORTUNISTI^ESKIE INFEKCII(B, (Nspid(B-(NSWQZANNYEs; (NsERODIAGNOSTIKAs; (NiNFEKCIONNYE BOLEZNI(B, (NBORXBAs; (NaRMENIQs